NURSING CARE IN EFFECTIVENESS OF BREATHING FOR CHRONIC OBSTRUCTION PATIENTS IN RSI NASHRUL UMMAH LAMONGAN - Dwi Anugrah, Annisa (Journal of Vocational Nursing, 2021)
Introduction: Air pollution can cause respiratory system disorders in the form of alveoli damage, airway, and lung tissue inflammation. Inflammation of the lungs can damage the respiratory tissue and stimulate excess sputum production which causes ineffective airway clearance. This process, if it takes a long time, causes irreversible structural damage to the airway wall. This condition can progress to severe airway obstruction, called COPD. This research aims to explain nursing care for patients with Chronic Obstructive Pulmonary Disease (COPD) in the Tuberose Room at RSI Nashrul Ummah Lamongan. Methods: The research design used in this research is case study research. Participants in the study  for Mr. "K" 69 years. The result of problem identification that arises is Chronic Obstructive Pulmonary Disease (COPD) with the main nursing diagnosis of Ineffective Airway Cleansing. Interventions that were emphasized and carried out in the field in cases were maintaining oxygen therapy, semi-fowler position, and administration of a nebulizer. The final evaluation of nursing diagnoses in patients was not resolved within the specified time. Result: Implementation of Nursing Care Ineffective Airway Cleansing of COPD patients in the Tuberose Room at RSI Nashrul Ummah Lamongan, there are still gaps with the literature. Conclusion: Suggestions for nurses are expected to be the focus of nurses in developing science to be applied to all nursing personnel in providing nursing care to ineffective airway cleaning for COPD patients.